Modified Endoscopic Distal Soft Tissue Procedure (mEDSTP) and Arthroscopic Lapidus Arthrodesis for Correction of Severe Hallux Valgus - Tun Hing Lui, M.B.B.S. (HK), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S.; Charles Churk Hang Li, M.B.Ch.B., M.R.C.S. (HK), F.R.C.S.Ed. (Ortho), F.H.K.C.O.S., F.H.K.A.M. (Ortho); Sui Kit Chan, M.B.B.S.; Amanda Mun Yee Slocum, M.B.B.S. (HK), M.R.C.S. (HK), F.R.C.S.Ed. (Ortho), F.H.K.C.O.S., F.H.K.A.M. (Ortho) (Arthroscopy Techniques, 2023)
Hallux valgus is one of the most common forefoot deformities faced by foot and ankle surgeons. Symptomatic deformity usually needs surgical correction. Endoscopic techniques of hallux valgus correction have been reported that are based on the same principle of the classic distal soft tissue procedure. Recently, the technique has been modified to include reconstruction of the medial metatarsosesamoid ligament and augmentation of the intermetatarsal ligament. In severe deformity or the presence of hypermobility or painful degeneration of the first tarsometatarsal joint, Lapidus arthrodesis of the joint is indicated. Arthroscopic Lapidus arthrodesis has been reported to reduce the complications associated with open procedure, including first metatarsal shortening, metatarsal elevatus, and nonunion. In this technical note, the technical details of a combined modified endoscopic distal soft tissue procedure and arthroscopic Lapidus arthrodesis is described. This is a minimally invasive approach for correction of severe hallux valgus deformity, especially that associated with ligamentous laxity.